Pengaruh Penggunaan Make-Up Sederhana Terhadap Kepercayaan Diri Wanita - Herlina, Fadilla (Jurnal Tata Rias, 2024)
This study aims to analyze the effect of simple makeup use on women's self-confidence through a literature review approach. Simple makeup is defined as minimal cosmetic use that maintains a natural appearance. This study collected and reviewed various literature from scientific journals, books, and relevant articles published within the last 10 years. The analysis focused on the relationship between simple makeup and self-confidence, considering psychological, social, and cultural aspects. The findings reveal that simple makeup positively influences women’s self-confidence, particularly in social and professional contexts. Simple makeup helps women feel more confident without altering their core identity. The study also found that beauty standards and social norms play a role in shaping women’s perceptions of makeup and self-confidence. This study concludes that simple makeup can serve as a tool to enhance women's self-confidence in everyday life. Further research is recommended to explore additional factors, such as age and cultural background, that may influence this relationship